MOTIVATION AS A SYSTEM-FORMING TOOL FOR IMPROVING THE PERFORMANCE RESULTS OF THE STAFF OF THE ENTERPRISE - ZELENA, Mariya; CHERNUSHKINA, Oksana; BAKSALOVA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines motivation as a system-forming tool for improving the results of the company's personnel. Work productivity, which determines the level of economic efficiency of the enterprise's functioning, is considered. Tasks that can be solved with the help of motivation at an industrial enterprise are defined. The practical experience of developed countries in increasing the interest of personnel in the results of work, strengthening their work motivation is considered. An overview analysis of the labor incentive bonus system, which is very popular among foreign employers, was carried out. Indicators and sizes for calculating the bonus for the performance of the main results of production and economic activity have been determined. A scale has been created for calculating the bonus. The size of the bonus reduction for employees of an industrial enterprise for violation of labor discipline was considered. The specified conditions under which the bonus is paid for the performance of a particularly important task. Formed types of bonuses that can be offered at an industrial enterprise. The main areas of stimulation of the workers of the industrial enterprise have been determined.
Keywords: personnel; personnel management; personnel motivation; performance results; bonuses